1921 Mo. Laws 693, § 3 - (:unkn) unknown (My University, 1921)
Weapons, Firearms: Regulation of Sale and Possession, § 3: No person within this state shall lease, buy or in anywise procure the possession from any person, firm or corporation within or without the state, of any pistol, revolver or other firearm of a size which may be concealed upon the person, that is not stamped as required by section 1 of this act; and no person shall buy or otherwise acquire the possession of any such article unless he shall have first procured a written permit so to do from the circuit clerk of the county in which such person resides, in the manner as provided in section 2 of this act.
Keywords: COMMERCIAL SALES REGULATION